Imagining A Healthy Democracy: Crafting Effective Responses To Electoral Manipulation (Jurnal Huma Betang Demokrasi, 2024)
The primary objective of this research is to provide a comprehensive analysis of manipulation strategies, motivations, patterns, and vulnerabilities within regional legislative elections in authoritarian contexts. We aim to challenge conventional wisdom, identify common patterns, and shed light on vulnerabilities that often go unnoticed. By doing so, we intend to enrich the discourse on electoral manipulation and lay the groundwork for more nuanced analyses and policy considerations in the future. To achieve our objectives, we employ the "Strategic Adaptation Theory" as a theoretical framework, which views manipulation as an adaptive response to changing political, social, and economic conditions. Our analysis challenges the prevailing notion that manipulation in authoritarian elections is solely an expression of regime strength. Instead, we find that manipulation often arises from uncertainty and adaptation to dynamic political landscapes. We categorize manipulation into four major strategies, identify common patterns in their use, and reveal the presence of a systemic logic guiding their deployment. Moreover, our study highlights the urban-rural divide in manipulation tactics, showing how electoral uncertainty varies with urbanization levels. Importantly, we emphasize the vulnerabilities that underlie seemingly strong authoritarian regimes. This research offers a more nuanced understanding of electoral manipulation and provides a foundation for policy considerations, ultimately enhancing our ability to address and potentially mitigate manipulation in authoritarian electoral processes.
Keywords: authoritarianism; electoral manipulation; regional legislative elections; strategic adaptation theory; vulnerabilities